Progranulin: a novel regulator of gastrointestinal cancer progression - DeMorrow, Sharon (Translational Gastrointestinal Cancer; Vol 2, No 3 (July 06, 2013): Translational Gastrointestinal Cancer, 2013)
Progranulin (PGRN) is a soluble factor that regulates cell proliferation, motility and inflammation. A role for PGRN in the progression of ovarian and breast cancers is well established. However, the expression and subsequent consequences of PGRN on the progression of gastrointestinal tumors is not well recognized. This review briefly summarizes our current knowledge of the mechanisms of action of PGRN and highlights the role of this signaling molecule in various gastrointestinal cancers.